Directional characteristic of a circular membrane vibrating under the effect of a force with uniform surface distribution - RDZANEK, Witold (Archives of Acoustics, 1985)
In this paper the acoustic pressure of a circular membrane is analysedon the assumption that the distance between the field point and the membrane is much longer, both in terms of its linear dimensions and the wavelengths radiated. It was assumed that the membrane was excited to induced harmonicvibration - including nonresonance one - by a force with uniform surfacedistribution. The membrane was placed in a rigid, planar baffle, and the gasmedium, into which it radiated, was 108s1088. Numerical examples of the directionalcharacteristic were represented graphically.